El Significado de la Marihuana para Cinco jovenes de Bogotá (2017)
The main objective of this research is to reveal the main meanings attributed to marijuana consumption by five young university consumers from the city of Bogotá. Marijuana consumption in recent years has been taken as a public health problem, since it is among the most consumed non-legal psychoactive substances around the world, a problem that involves society from different perspectives. contexts (family, social, cultural) hence the importance of the present study, in order to establish the different meanings that young people can contribute as marijuana consumers.